Redefining fine roots improves understanding of below‐ground contributions to terrestrial biosphere processes. Issue 3 (10th March 2015) - McCormack, M. Luke; Dickie, Ian A.; Eissenstat, David M.; Fahey, Timothy J.; Fernandez, Christopher W.; Guo, Dali; Helmisaari, Heljä‐Sisko; Hobbie, Erik A.; Iversen, Colleen M.; Jackson, Robert B.; Leppälammi‐Kujansuu, Jaana; Norby, Richard J.; et al.
<x xml:space="preserve">Abstract</x> <table-wrap position="anchor" orientation="portrait"> 505 I. I. 506 II. II. 506 III. III. 508 IV. IV. 512 V. V. 513 VI. VI. 514 515 References 515 </table-wrap> Summary Fine roots acquire essential soil resources and mediate biogeochemical cycling in terrestrial ecosystems. Estimates of carbon and nutrient allocation to build and maintain these structures remain uncertain because of the challenges of consistently measuring and interpreting fine‐root systems. Traditionally, fine roots have been defined as all roots ≤ 2 mm in diameter, yet it is now recognized that this approach fails to capture the diversity of form and function observed among fine‐root orders. Here, we demonstrate how order‐based and functional classification frameworks improve our understanding of dynamic root processes in ecosystems dominated by perennial plants. In these frameworks, fine roots are either separated into individual root orders or functionally defined into a shorter‐lived absorptive pool and a longer‐lived transport fine‐root pool. Using these frameworks, we estimate that fine‐root production and turnover represent 22% of terrestrial net primary production globally – a c. 30% reduction from previous estimates assuming a single fine‐root pool. Future work developing tools to rapidly differentiate functional fine‐root classes, explicit incorporation of mycorrhizal fungi into fine‐root studies, and wider adoption of a two‐pool approach to model fine roots provide opportunities to better understand below‐ground processes in the terrestrial biosphere.